PEMBERITAAN PEMBANGUNAN BANDARA DI KECAMATAN TEMON KABUPATEN KULONPROGO - Zaka Putra Ramdani (Profetik: Jurnal Komunikasi, 2014)
The local newspaper provides a set of value which is relevant to it’s readers’ characteristics due to their closeness with the issues which has been issued. Two of many local newspapers in Yogyakarta are Kedaulatan Rakyat and Harian Jogja. Both of them had issued the planning to build new airport in Temon subdistrict, Kulonprogo regency, Yogyakarta province, since November 2013 until January 2014. They issued about the controversy regarding this planning between Wahana Tri Tunggal (WTT) association and the goverment of Kulonprogo regency. This research applies framing analysis of Zhongdang Pan and Gerald M. Kosicki to explain the mass media construction on the planning to build new airport,through the news issued byKedaulatan Rakyat and Harian Jogja. Framing analysis of Pan and Kosicki consists of four framing sets or main structures for the unit analysis: syntax structure, script structure, thematic structure, and retoric structure. The result reveals that despite theirs standing positions as the same local newspaper in Yogyakarta province, Kedaulata Rakyat and Harian Jogja have different framing on issuing the planing to build new airport in Temon subdistrict. Kedaulatan Rakyat constructsthat the plan to build new airport in Temon subdistrict will benefit the society of Temon subdistrict. On the contrary, Harian Jogja contructs that this planning, will harm the society of Temon subdistrict.